Design And Production Of Fertilizer Application Scheduling Using Earliest Due Date In Gemah Ripah Loh Jinawi Industry - Setyawati, Nina; Eko Wulandari, Sri Hariani; Churniawan, Agus Dwi (Jurnal Sistem Informasi Universitas Dinamika (JSIKA), 2016)
PT Gemah Ripah Jinawi OIndustri Loh is a company engaged in the fertilizer industry, phosphate and fertilizers dolomite. The Company only accepts orders with system orders from customers. In doing so, the production of fertilizers, the company was late in completing orders received in this case because the data recording customer orders are not yet integrated with production scheduling system. In addition to knowing the time needed to complete the production orders, the company only estimate how much time the production is done can be completed prior to the maturity date of a customer request. Of the problems that occur can be solved by using fertilizer production scheduling application with the method earliest due date (EDD) that minimizes delays. Application of fertilizer production scheduling applications using the earliest due date (EDD) to assist and optimize production scheduling in accordance with the capacity of existing machines so that customer orders will be fulfilled.